Fotovideo framework: school resource center - Rahmat, Nur Rawaidah; Adnan, Amir Hamzah (Universiti Teknologi MARA, Kedah, 2019)
In line with the development of education and with the industrial revolution 4.0, the school resource center has to play an important role in shaping the outcome of special needs student. As a result, SM Pendidikan Khas Vokasional Merbok Resource Center has created FotoVideo Club that has been formulated in line with the concept of digital literacy to add additional knowledge and skills as well as specialization in learning that enables them to prepare for the world of work.